2017
DOI: 10.1039/c7ra02955a
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of extraction and biological evaluation of naturally occurring sugar-mimicking sulfonium-ion and their synthetic analogues as potent α-glucosidase inhibitors from Salacia: a review

Abstract: A review of the selective inhibitory activities of sulfonium compounds ofSalaciaagainst intestinal α-glucosidases, structural features important for effective inhibition and the toggling approach for controlling starch digestion and glucose release.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 107 publications
0
10
0
Order By: Relevance
“…α-Glucosidase inhibition in the small intestine is a simple and effective way by which hyperglycemia treatment can manage type 2 DM . It was reported that different sources of phenolics play a role in inhibiting α-glucosidase; for instance, examples of such phenolics include anthocyanidin derivative from blueberry, blackcurrant, and blue honeysuckle fruits, catechins derivative derived from green tea, and rosmarinic acid derived from Perilla frutescens. , Hence, it was of interest to explore whether the phenolics in the cultivated P.…”
Section: Resultsmentioning
confidence: 99%
“…α-Glucosidase inhibition in the small intestine is a simple and effective way by which hyperglycemia treatment can manage type 2 DM . It was reported that different sources of phenolics play a role in inhibiting α-glucosidase; for instance, examples of such phenolics include anthocyanidin derivative from blueberry, blackcurrant, and blue honeysuckle fruits, catechins derivative derived from green tea, and rosmarinic acid derived from Perilla frutescens. , Hence, it was of interest to explore whether the phenolics in the cultivated P.…”
Section: Resultsmentioning
confidence: 99%
“…To date, several research groups have performed synthetic and structure-activity relationship (SAR) studies of salacinol (1) and related analogues regarding α-glucosidase inhibitory activity [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55]. We are also performing subsequent studies on the total syntheses of these sulfonium constituents (1-8) and their highly active analogues, as well as more detailed SAR studies [38,[56][57][58][59][60][61][62]; those data will be summarized separately.…”
Section: Thiosugar Sulfoniums (1-6) As a Novel Class Of α-Glucosidase Inhibitorsmentioning
confidence: 99%
“…25−32 biological evaluation of 4−11 indicated an equal α-glucosidase inhibitory potency compared with clinically used α-glucosidase inhibitors. 33 In silico docking clearly demonstrated a strong electrostatic interaction between sulfonium cation and specific carboxylate ion located at a certain catalytic pocket of αglucosidase. 34 Experiment using an in situ rat ligated intestinal loop model revealed that these sulfonium salts are hardly absorbed from the rat intestine.…”
Section: ■ Introductionmentioning
confidence: 98%
“…Ever since the late 1990s, a group of sulfonium salts 4 – 11 (Figure ) have been isolated from genus Salacia , a herbal medicine traditionally used for the treatment of T2DM in South Asian countries. 4 , 5 , 6 , and 7 present a unique zwitterionic inner salt structure while 8 , 9 , 10 , and 11 are identified as their de- O -sulfonated analogues, respectively. A biological evaluation of 4 – 11 indicated an equal α-glucosidase inhibitory potency compared with clinically used α-glucosidase inhibitors . In silico docking clearly demonstrated a strong electrostatic interaction between sulfonium cation and specific carboxylate ion located at a certain catalytic pocket of α-glucosidase .…”
Section: Introductionmentioning
confidence: 99%